Light-Driven Hydrogel Microactuators for On-Chip Cell Manipulations - Koike, Yuha; Yokoyama, Yoshiyuki; Hayakawa, Takeshi (Frontiers in Mechanical Engineering, 2020)
We present a driving method for on-chip hydrogel microactuators developed to be used for single-cell manipulations. The hydrogel actuator is composed of a temperatureresponsive gel coated on a glass substrate with light-absorbing micropatterning. The actuator is driven by light irradiation, which increases its temperature. The advantage of this driving method is twofold: allowing local heating of the actuator while decreasing heat dissipation to the substrate and its environment. The local heating induced by light irradiation improves the response characteristics of the hydrogel microactuator because the slight increase in environmental temperature aids cooling of the microactuator when the light is turned off. Furthermore, local heating enables multiple actuators to be located in close proximity without unintentionally actuating neighboring actuators through heat dissipation. In addition, the heating induced by the light irradiation does not require wiring on the chip. Therefore, the developed driving method enables the integration of a large number of actuators that can be independently driven on a single chip.